KEANEKARAGAMAN TUMBUHAN ANGIOSPERMAE DI LINGKUNGAN KAMPUS FMIPA UNIVERSITAS NEGERI PADANG - Annisa Khairani; Moralita Chatri (Jurnal Biogenerasi, 2026)
Angiosperms are a group of closed seed plants that have an important role in maintaining the balance of the ecosystem, especially in the campus environment that functions as a green open space. This study aims to know the diversity of Angiosperms found in the Faculty of Mathematics and Natural Sciences (FMIPA) Campus environment, Padang State University (UNP). The method used is direct observation with exploration techniques in several locations of the FMIPA campus. The data collected include local names, scientific names, families, and classifications of Angiosperms. The results of the observations show that the FMIPA UNP Campus environment has a fairly high diversity of Angiosperms, consisting of various monocot and dicot species originating from various families. This diversity is influenced by environmental conditions, management of campus green spaces, and the use of plants as ornamental plants, shade plants, and medicinal plants. The presence of Angiosperms in the campus environment plays an important role in supporting ecological, aesthetic, and educational functions.